2017
DOI: 10.1242/dev.146563
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional precision and accuracy in development: from measurements to models and mechanisms

Abstract: During development, genes are transcribed at specific times, locations and levels. In recent years, the emergence of quantitative tools has significantly advanced our ability to measure transcription with high spatiotemporal resolution in vivo. Here, we highlight recent studies that have used these tools to characterize transcription during development, and discuss the mechanisms that contribute to the precision and accuracy of the timing, location and level of transcription. We attempt to disentangle the disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 171 publications
1
32
0
Order By: Relevance
“…Predictions with this model on a large-scale basis, however, are far from perfect (Segal et al, 2008). As experimental tools are becoming more sophisticated, complex relationships between TF binding sequences, TF occupancy, and transcript abundance are being found, thus suggesting that sequence-controlled TF occupancy may not directly convert into transcription rate (Spitz and Furlong, 2012;Bentovim et al, 2017). For example, in two Drosophila species, Khoueiry et al (2017) found conserved combinatorial TF occupancy despite sequence divergence, and conserved enhancer function despite diverged occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions with this model on a large-scale basis, however, are far from perfect (Segal et al, 2008). As experimental tools are becoming more sophisticated, complex relationships between TF binding sequences, TF occupancy, and transcript abundance are being found, thus suggesting that sequence-controlled TF occupancy may not directly convert into transcription rate (Spitz and Furlong, 2012;Bentovim et al, 2017). For example, in two Drosophila species, Khoueiry et al (2017) found conserved combinatorial TF occupancy despite sequence divergence, and conserved enhancer function despite diverged occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Tbx1/10 and Ebf , spatially and temporally accurate activation is essential to permit the emergence of first and second cardiac, and pharyngeal muscle lineages 14,15,17,43 . We propose that, whereas the activity of multiple elements with similar spatio-temporal transcriptional outputs permits precise and robust gene activation 67,79 , the modular organization of the cis -regulatory system increases the repertoire of regulatory inputs, acting through both accessibility and activity, to control cell-specific gene expression. These multi-level combinatorial inputs achieve exquisite spatio-temporal control, while permitting strong activation, thus ensuring both transcriptional precision and accuracy for developmental fate choices (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These attempts range from modeling a monotone gradient (Gregor et al, 2007), to quantifying variation in gene expression patterns Fowlkes et al, 2008;Knowles, 2012;Martinez-Abadias et al, 2018). To our knowledge, however, very few (Bentovim et al, 2017;Park et al, 2019) used comprehensive descriptors to thoroughly extract more information than possible from qualitative approaches, or exploited the statistical power offered by such descriptors. This prompted us to implement a generic quantitative framework to measure and compare activity levels of the spot 196 enhancer across the wing among genotypes, and use powerful statistical tools to test the significance of the differences.…”
Section: Quantitative Assessment Of Gene Expression To Decipher Regulmentioning
confidence: 99%